Modeling the Relationship of Net Atomic Charge with the Activity of 5-Aminopyrazole Derivative Compounds as Antioxidants with AM1 Method - Nagmah Putri Dinda Toni; Fajriah Azra; Mirella Fonda Maahury (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2022)
This study was conducted to analyze the quantitative relationship between structure and net atomic charge modeling activity of 21 5-aminopyrazole derivatives as antioxidants. This study aims to determine the value of the net atomic charge and obtain the best HKSA equation. The method used in this study is the semi-empirical method of Austin Model 1 with geometry optimization. The selection of the best equation model is done by statistical analysis using the method of correlation analysis and multiple regression with Backward to the calculated descriptor data. From the results of the study, it was found that model 1 as the HKSA equation model was chosen with the equation Log IC50 = Log IC50 = 1.648+(0.914*qN1)-(3.662*qN2)-(1.99*qC3)+( 0.004*qC4)+(1.052* qC5 )+(1.226*qN6) where n = 6 ; R = 0.724 ; R2 = 0.524 ; SE = 0.1462 ; Sig = 0.068 ; PRESS = 0.2994. This study shows that atomic charge plays an important role in enhancing antioxidant activity.